Pengembangan Bahan Ajar IPA Digital Berbasis Model Discovery Learning untuk Meningkatkan Kemampuan Berpikir Tingkat Tinggi Materi Sistem Pencernaan Manusia Kelas V SD - Septianti Putri, Elvira; Widi Winarni, Endang; Muktadir, Abdul (Jurnal Kajian Pendidikan Dasar, 2025)
The purpose of this study was to describe the characteristics, feasibility, user responses and analyze the effectiveness of digital science teaching materials based on discovery learning with digital science teaching materials to improve students' high order thinking skills. The type of research used is research and development. The research model in the development of teaching materials is the ADDIE model. The types of data collected are quantitative and qualitative data using instruments in the form of document analysis sheets, interview guidelines, observation validation sheets, and test sheets. Based on the results of the study, it can be concluded that the digital science teaching materials developed are suitable for use as teaching materials in Natural Sciences (IPA) subjects, namely the human digestive system. The validated points include the feasibility of the material, language, and design. The percentage of material validation results is 75%, linguist validation is 75% and design expert validation is 50%. The response of grade V students of SDN 119 Rejang Lebong is very good because based on the results of the questionnaire analysis of grade V students' responses, it is 83%. The teaching materials developed are effective in improving the high order thinking skills of grade V students of SDN 119 Rejang Lebong. This is based on the results of N-Gain effectiveness of 77% or level at level C4 of 80%, level C5 of 73%, level C6 of 79%.